Gravitational entropy of wormholes with exotic matter and in galactic halos - Lima, R. de C. [UNESP]; Nogales, Jose A. C.; Pereira, S. H. [UNESP] (World Scientific Publ Co Pte Ltd, 2020)
In this work, we study and compare the features of gravitational entropy near the throat of transversable wormholes formed by exotic matter and wormholes in galactic halos. We have verified that gravitational entropy and entropy density of these wormholes in regions near their throats are indistinguishable for objects of same throat, despite the fact that they are described by different metrics and by distinct energy-momentum tensors. We have found that the gravitational entropy density diverges near the throat for both cases, probably due to a nontrivial topology at this point, however, allowing the interesting interpretation that a maximum flux of information can be carried through the throat of these wormholes. In addition, we have found that both are endowed with an entropic behaviour similar to Hawking-Bekenstein's entropy of nonrotating and null charge black holes.
Keywords: Wormholes; gravitational entropy; galactic halos